#TITLE_ALTERNATIVE# - BARNES (NIM 15107027); Pembimbing: Dr. Deni Suwardhi, ST., MT. dan Dr.Ir. Agung Budi Harto, M., AHMAD
Digital reconstruction of 3D object at close range needed in different applications, such as industrial, medical and cultural heritage. To reconstruct a digital object can be achieved with existing methods, there are laser scanning and Photogrammetry close ranges (FRD). Both of these methods provide data which is called the point cloud represents the surface of the object. In the FRD, lots of software that can do this, among them are commercial software, photomodeler scanner, open source local software, bundler, open source remote software, my3Dscanner. All of the products of from software photogrammetry is to be compared and be integrated with the result of a method of a laser scanning. The results of the research show that a method of laser scanning point cloud that produces more dense point cloud compared to FRD method. The result of obtained from the comparison software FRD, photomodeler scanner and bundler produce point cloud that more tightly compared software my3dscanner.